Development of validated stability-indicating chromatographic method for the determination of fexofenadine hydrochloride and its related impurities in pharmaceutical tablets - Maher, Hadir M (BioMed Central, 2011)
A simple reversed phase high performance liquid chromatographic method with diode array detector (HPLC-DAD) has been developed and subsequently validated for the determination of fexofenadine hydrochloride (FEX) and its related compounds; keto fexofenadine (Impurity A), meta isomer of fexofenadine (Impurity B), methyl ester of fexofenadine (Impurity C) in addition to the methyl ester of ketofexofenadine (Impurity D). The separation was based on the use of a Hypersil BDS C-18 analytical column (250 × 4.6 mm, i.d., 5 μm). The mobile phase consisted of a mixture of phosphate buffer containing 0.1 gm% of 1-octane sulphonic acid sodium salt monohydrate and 1% (v/v) of triethylamine, pH 2.7 and methanol (60:40, v/v). The separation was carried out at ambient temperature with a flow rate of 1.5 ml/min. Quantitation was achieved with UV detection at 215 nm using lisinopril as internal standard, with linear calibration curves at concentration ranges 0.1-50 μg/ml for FEX and its related compounds. The optimized conditions were used to develop a stability-indicating HPLC-DAD method for the quantitative determination of FEX and its related compounds in tablet dosage forms. The drugs were subjected to oxidation, hydrolysis, photolysis and heat to apply stress conditions. Complete separation was achieved for the parent compounds and all degradation products. The method was validated according to ICH guidelines in terms of accuracy, precision, robustness, limits of detection and quantitation and other aspects of analytical validation.